2009
DOI: 10.1021/ac900611a
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Stabilization of Noncovalent Protein Complexes Formed by Electrospray Ionization

Abstract: The use of gas phase additives to stabilize noncovalent protein complexes in electrospray ionization mass spectrometry (ES-MS) is demonstrated for two protein-ligand interactions, an enzyme-small molecule inhibitor complex, and a protein-disaccharide complex. It is shown that the introduction of gas phase imidazole into the ES ion source effectively protects gas phase protein-ligand complexes against in-source dissociation. The stabilizing effect of imidazole vapor is comparable to that observed upon addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 22 publications
2
81
0
Order By: Relevance
“…For example, some PL complexes, which are stabilized by strong ionic interactions in solution, exhibit low gas phase stabilities [47], while some PL complexes formed by hydrophobic bonding are quite stable in the gas phase [23,50,51]. Collisional heating of gaseous ions may occur at various stages during the ion sampling process, such as within the heated metal sampling capillary (if used), in the nozzle (or orifice)-skimmer region, and during accumulation of ions within external rf multipole storage devices (e.g., hexapole) [14,36,47,50,51]. Usually, the occurrence of in-source dissociation can be identified from changes in R resulting from changes in ion source parameters, in particular voltage differences in regions of high pressure (e.g., nozzle-skimmer voltages), that influence the internal energy of the ions.…”
Section: In-source Dissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some PL complexes, which are stabilized by strong ionic interactions in solution, exhibit low gas phase stabilities [47], while some PL complexes formed by hydrophobic bonding are quite stable in the gas phase [23,50,51]. Collisional heating of gaseous ions may occur at various stages during the ion sampling process, such as within the heated metal sampling capillary (if used), in the nozzle (or orifice)-skimmer region, and during accumulation of ions within external rf multipole storage devices (e.g., hexapole) [14,36,47,50,51]. Usually, the occurrence of in-source dissociation can be identified from changes in R resulting from changes in ion source parameters, in particular voltage differences in regions of high pressure (e.g., nozzle-skimmer voltages), that influence the internal energy of the ions.…”
Section: In-source Dissociationmentioning
confidence: 99%
“…In cases where gentle sampling conditions do not eliminate the occurrence of in-source dissociation, the employment of stabilizing additives may prove beneficial. For example, the addition of imidazole to solution, at high concentration (91 mM), has been shown to prevent gas phase dissociation of the ions of a number of different PL interactions, including protein-carbohydrate, protein-fatty acid, and protein-small molecule complexes [23,47,50]. The origin of the stabilizing effects of imidazole is believed to be due, at least in part, to enhanced evaporative cooling resulting from the dissociation of nonspecific imidazole adducts from the gaseous PL ions [47].…”
Section: In-source Dissociationmentioning
confidence: 99%
“…In extreme cases, in-source dissociation results in false negatives, wherein no ligand-bound protein ions are detected by ESI-MS [15]. However, using gentle sampling conditions, along with stabilizing solution or gas phase additives, it is sometimes possible to preserve the labile protein-ligand complexes during ESI-MS analysis and to quantify their association constants [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the extreme case, where no PL ions survive, in-source dissociation will result in a false negative. Recently, it was shown that solution or gas-phase additives can, in some instances, protect complexes from in-source dissociation [12,15]. However, this approach does have its limitations and the detection of very labile gas-phase complexes, which rapidly dissociate at ambient temperature, by ES-MS remains problematic.…”
mentioning
confidence: 99%